Cafe marketing communication based on sustainability - environmentally friendly of kopi nako alam sutera - Tirta Mulyadi; Ana Rusmardiana; Muhammad Reza Aulia; Dewi Yanti; Dendi Zainuddin Hamidi (Jurnal Komunikasi Profesional, 2023)
Coffee Shop and working are two same categories in people’s daily activity. Young generation likes to perform their work from any place especially coffee shop. To them, coffee shops are like a mold for their soul where they can share stories, hangout, make a deal, etc. Kopi Nako Alam Sutera; who’s not only Sustainable coffee shop but also presenting workspace comfortability and also lactose intolerant product. The quality of Kopi Nako’s variant of service had proven to us the ability to commit to sustainability despite managing middle business-like Coffee Shop. Kopi Nako breaks the stigma that middle business doesn’t have knowledge to contribute to sustainability program.